The Origins of Buddhism (Shishi Yuanliu) and Illustrated Hagiographic Narratives in Ming China - Ganany, Noga (Journal of Chinese religions, 2025)
The fifteenth-century Origins of Buddhism (or "Origins of the Śākya Clan," Shishi yuanliu《 釋氏源流》, hereafter SSYL) narrates the Life of the Buddha Śākyamuni and the history of Chinese Buddhism in four hundred illustrated episodes, each occupying one page in the "picture-above-text" format. This article examines the compilation strategy of SSYL and its broader impact on Chinese book culture during the Ming dynasty. A highly selective collage that is both polemical and syncretic, SSYL propagates a grand vision of Buddhism that draws on the realms of genealogy, hagiography, and historiography. Beyond its great significance to East Asian Buddhism, SSYL also represents an important milestone in the development of Chinese publishing, particularly significant to the emergence of illustrated accounts of "origins" (yuanliu 源流 and chushen 出身) in anthologies, encyclopedias, and literary works that present cultic traditions as rooted in the life stories of revered patriarchs.